Currency crises, sunspots and exchange-rate overshooting - Inchauspe, Julian (World Business Institute, 2009)
This paper provides a macroeconomic framework for theoretical and empirical analysis of the role of sunspots and shock-dependent expectations in currency crises. The model distinguishes between macroeconomic fundamentals and shock expectations as cause of currency crises. It is assumed that good prices are sticky so that the economy responds to information through the exchange rate or, when it is fixed or managed, through the interest rate. I argue that, under certain conditions, pessimistic expectations can be strong enough to self-validate and bring about crises.